STUDY REGARDING THE ALLOCATION OF PRODUCTION OVERHEADS PROCEDURE: CONVENTIONALITY, SUBJECTIVITY AND INFORMATION DISTORTION IN MANAGERIAL ACCOUNTING - GUINEA FLAVIUS-ANDREI (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie, 2017)
Traditional methods of cost calculating have become obsolete. The loss of relevance of traditional cost calculating systems is mainly due to the existence of a gap between the current model of enterprise control and the model of analysis centres, as well as the difference between the way of composing the actual cost and its image reflected by managerial accounting. The vision of the company on which the method of analysis centres was based no longer corresponds to the present reality. The approach of this study captures the complex and delicate subject of the allocation of production overheads procedure. Through the field research undertaken, it was aimed to identify and possibly solve the problems related to the rational allocation of these expenditures. The own contributions of the study are highlighted in particular at practical level, as an obvious result of the types of research undertaken. One of the fundamental objectives of the present study is to enhance the interest regarding the practical possibilities of protecting against the dangers of a creative managerial accounting system. A managerial accounting system, once implemented, will also attract the manifestation of creative accounting phenomena, especially in times of crisis. Having at their disposal the most relevant set of information, managers are tempted to resort to more or less ingenious techniques that are more or less questionable and more or less legal, in order to improve the financial statement presentation.